SANCTIONS FOR THOSE WHO REFUSE COVID-19 VACCINATION UNDER PRESIDENTIAL REGULATION NO. 14/2021: A PATIENT’S THERAPEUTIC RIGHTS PERSPECTIVE - Bagaskara, Ilham Perdana; Efendi, Dr. Jonaedi (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
This research aims to examine the applicable law against people who refused the Covid-19 vaccines during several problems and side effect that arises. The research method that will be used by the researcher in compiling this thesis is using juridical-normative method, statutory and conceptual approach. The researchers used several norms and regulations based on government and president in conducting this research. The patient's right in basic therapeutic contract is the right to obtain information from medical services, and also the right to consent to medical treatment to be given to the patient and the risks of medical action by the doctor. There is an administrative penalize for whom refused Covid-19 vaccine that had been regulated in Presidential Regulation No. 14/2021, but WHO stated that the obligation to do Covid-19 vaccination will cause an impact that will trigger someone to be indifferent and anticipate the COVID-19 vaccine dan it also makes dissension of opinion in society which considers that the government has violated the patient’s therapeutic rights based on the relevant laws.